2017
DOI: 10.4103/jets.jets_42_17
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis: How reliable are the cutaneous signs?

Abstract: Necrotizing fasciitis (NF) is a surgical emergency. It is often aggressive and characterized by the rapidly progressive inflammatory infection of the fascia that causes extensive necrosis of the subcutaneous tissue and fascia, relatively sparing the muscle and skin tissue. As the disease progresses, thrombosis of the affected cutaneous perforators subsequently devascularizes the overlying skin. The course indeed can be a fulminant one. The diagnosis of NF, especially in the early stages, is extremely challengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…erysipelas and cellulitis) in the early stage, but some clinical features (such as warmth, swelling, induration, and poorly defined margins) are helpful in diagnosis. 3 Laboratory investigations are also essential tools for the diagnosis of NF. The Laboratory Risk Indicator for NF (LRINEC) is assessed by six routine laboratory tests and used initially to make an early distinction between NF and other soft tissue infections, and it is also a helpful tool for early diagnosis of NF.…”
Section: Discussionmentioning
confidence: 99%
“…erysipelas and cellulitis) in the early stage, but some clinical features (such as warmth, swelling, induration, and poorly defined margins) are helpful in diagnosis. 3 Laboratory investigations are also essential tools for the diagnosis of NF. The Laboratory Risk Indicator for NF (LRINEC) is assessed by six routine laboratory tests and used initially to make an early distinction between NF and other soft tissue infections, and it is also a helpful tool for early diagnosis of NF.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic assessment is beneficial for diagnosing NSTIs, since clinical symptoms are not seldom unreliable [4, 5, 19]. A prior study showed that macroscopic fascial necrosis during surgical exploration has a high positive predictive value, but a low negative predictive value and therefore cannot simply rule out NSTIs [7].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is imperative for clinicians to swiftly differentiate between these two clinical entities as treatment strategies and prognosis vary significantly. NF patients may also report tenderness, pain, hemodynamic stability, and tissue necrosis [24,25,26]. The pain tends to be out of proportion to the physical findings and patients might encounter sensory loss at the site of involvement.…”
Section: Andandmentioning
confidence: 99%
“…Within 1--2 days of the infection, bullae and vesicles may begin to form, accompanied by serosanguinous leakage (intermediate stage of NF), followed by skin necrosis and crepitus (late stage) [29,30 ▪ ]. While bullae formation is observed in 44.5% of cases, skin necrosis and crepitus occur less frequently, at 23.5 and 4.9%, respectively [24]. In type II NSTI, patients’ superficial injuries may go unnoticed until extensive tissue damage has occurred.…”
Section: Diagnosismentioning
confidence: 99%